STATE OF GASTRIC MICROBIOCENOSIS IN PATIENTS WITH REACTIVE ARTHRITIS ACCORDING TO THE DATA OF A PROSPECTIVE STUDY - Kamilla Erkinovna Azadaeva; Nigora Khasanovna Tukhtaeva; Gulnoza Kutpitdinovna Rakhmatullaeva; Mavjuda Xalmatovna Tagaeva; Zulfiya Sanatovna Maksudova (Journal Park Publishing, 2023)
It is known that the stomach, like other parts of the digestive tube, has its own microbiotic system, which may be involved in providing colonization resistance of the stomach. If we take this fact into account, it becomes obvious that the defeat of the GDZ, identified by us, is possibly associated with certain shifts in this system. Materials and methods: A prospective study was conducted in 52 patients with ReA of urogenic and enterogenic etiologies treated in the rheumatology department of the TMA clinic. The patients were divided into 3 groups depending on the presence of pathology of the gastroduodenal zone: the 1st group - patients with ReA who did not complain about the digestive system; 2nd group - patients with ReA presenting complaints from the GDZ lesion, but not having a history of GDZ pathology; the 3rd group - patients with ReA with GD pathology. The state of microbiocenosis of the gastroduodenal zone of the luminal and mucosal microflora of the stomach was assessed by taking biopsy material by gastroduodenal sounding. Statistical data processing was carried out using the EXEL package.
Keywords: reactive arthritis, prospective study, microbiocenosis of the gastroduodenal zone.